Contribution of KWT Gardens to Plant Biodiversity and Carbon Stock in Bogor City - Fatin, Amirah Naura; Kaswanto, Kaswanto; Nurhayati, Nurhayati (SOCA: Jurnal Sosial Ekonomi Pertanian, 2025)
The phenomenon of urban sprawl in Bogor City has led to land-use changes and the expansion of residential areas, resulting in the reduction of green and agricultural lands that function as ecological buffers and providers of urban landscape services. KWT (Kelompok Wanita Tani or Women Farmer Groups) Gardens represent existing Green Open Spaces (Ruang Terbuka Hijau/RTH) in Bogor City that adopt a mixed garden or agroforestry system. This study aims to analyze the contribution of KWT gardens to plant biodiversity and carbon stock in Bogor City as a means of enhancing urban landscape services. Data were collected from six KWT gardens located in six districts across Bogor City. Plant composition and carbon stock data were obtained through field inventory and analyzed using a web-based tool, MyTree. The results show that vertically, the plant composition in KWT gardens is dominated by Stratum I vegetation (0–1 m) at 87.95%, while horizontally, the gardens are dominated by vegetable crops, accounting for 42.63% of the total. The highest tree carbon stock was found in KWT MM at 928.49 kg on a land area of 0.14 ha, while the lowest was in KWT AZ at 233.08 kg on a land area of 0.06 ha. KWT gardens using agroforestry systems contribute to enhancing plant biodiversity and carbon storage, which benefit urban communities both directly and indirectly.